RNA silencing: methods and protocols - Carmichael, Gordon G.; Carmichael, Gordon (Methods in molecular biology, 2005)
Identification of components of RNAi pathways using the tandem affinity purification method / Mikiko C. Siomi and Haruhiko Siomi -- Separation of drosophila RNA silencing complexes by native gel electrophoresis / John W. Pham and Erik J. Sontheimer -- Preparation and analysis of drosha / Yoontae Lee and V. Narry Kim -- RNA interference in Caenorhabditis elegans / Nathaniel R. Dudley and Bob Goldstein -- Down-regulating gene expression by RNA interference in Trypanosoma brucei / Christine E. Clayton ... [et al.] -- Analysis of double-stranded RNA and small RNAs involved in RNA-mediated transcriptional gene silencing / M. Florian Mette ... [et al.] -- Strategies for the design of random siRNA libraries and the selection of anti-GFP siRNAs / Mouldy Sioud and Sebastiona Wulchli -- Silencing gene expression with dicer-generated siRNA pools / Jason W. Myers and James E. Ferrell, Jr. --